The factorization method for inverse scattering by a two-layered cavity with conductive boundary condition - Ye, Jianguo; Yan, Guozheng (IMA journal of applied mathematics, 2022)
Abstract In this paper we consider the inverse scattering problem of determining the shape of a two-layered cavity with conductive boundary condition from sources and measurements placed on a curve inside the cavity. First, we show the well-posedness of the direct scattering problem by using the boundary integral equation method. Then, we prove that the factorization method can be applied to reconstruct the interface of the two-layered cavity from near-field data. Some numerical experiments are also presented to demonstrate the feasibility and effectiveness of the factorization method.